(untitled) (Rassegna di Diritto, Legislazione e Medicina Legale Veterinaria, 2018)
The Authors present the new EU Regulation n. 429/2016 on Animal Health in the hippiatric field, with the aim of highlighting the appropriate guidelines for the SSN veterinarian on communicable infectious diseases of equidae subjected to reporting obligations. The work is articulated in macro-chapters, including the detailed description of the new Animal Health Law, emerging diseases and the concept of disease notification. In this way, we want to provide support to the Official veterinarian, and to increase the level of knowledge of the application the new regulation and the compliance with it